L-methionine inhibits reaction of DNA with anticancer cis-diamminedichloroplatinum(II) - Vrana, Oldrich; Brabec, Viktor (Biochemistry, 2002)
Sufficient evidence has accumulated to identify DNA as the relevant pharmacological target of antitumor cisplatin [cis-diamminedichloroplatinum(II)]. This drug is administered intravenously so that before it reaches DNA in the nucleus of tumor cells it may interact with various compounds including sulfur-containing molecules such as L-methionine or the compounds containing these residues. L-Methionine increases the rate of reaction of cisplatin with monomeric guanosine 5'-monophosphate, and it was suggested on the basis of these results previously obtained by other authors that methionine residues could mediate the transfer of platinum onto DNA. We studied in the present work the reactions of the 1:1 complex formed between cisplatin and L-methionine or N-acetyl-L-methionine with synthetic, single- and double-stranded oligodeoxyribonucleotides and natural, high molecular mass DNA by using high-pressure liquid chromatography and flameless atomic absorption spectrophotometry. The results demonstrate that both L-methionine and N-acetyl-L-methionine decrease the rate of reaction of cisplatin with base residues in natural, high molecular mass DNA. Thus, the possibility that cisplatin bound to methionine residues serves as a drug reservoir available for platination of DNA in the nucleus of tumor cells appears unlikely.
Keywords: Oligodeoxyribonucleotides; cisplatina; Cisplatin; Antineoplastic Agents; Methionine; Nucleic Acid Heteroduplexes; kompetitivní vazba; protinádorové látky; oligodeoxyribonukleotidy; Binding, Competitive; methionin; makromolekulární látky; heteroduplexy nukleové kyseliny; Macromolecular Substances; molekulová hmotnost; DNA; Molecular Weight; deoxyguaninnukleotidy; Deoxyguanine Nucleotides; DNA, Single-Stranded; jednovláknová DNA